Folktales as a Means of Ecological Education for Society in Bejiharjo Village, Gunungkidul, Yogyakarta - Mei Latipah; Dyah Kemala F; Dyah Ayu P; Haryanto Haryanto; Ari Kusmiatun (Pancaran Pendidikan, 2017)
Literature and society are closely connected. Literature arises, grows, and thrives in the society. One of the examples is a folktale which exists as one of the literary works that contain many messages. Bejiharjo Village located in Gunungkidul subdistrict, the special region of Yogyakarta, possesses a lot of folktales describing its indigenous traditions. The local indigenous traditions reflect moral values held by the society. One of the moral values is about ecology. The Bejiharjo’s folktales related to the environment are Asal – usul Bersih Kali, Asal – usul Goa Sriti, and Tragedy Kali Semilih. These traditions and stories have proven that the people still preserve and cling to their culture. Moreover, it also can be utilised as a means of ecological education for the society. This study discusses folktales contained environmental which can be used as a good carrier of messages in order to maintain the natural surroundings. Moreover, through these folk tales, people are made aware of the important existence of the environment in human lives. Then, the traditions are not only to be followed, but also to be understood its meaning through the folktales. The value of ecological education that is contained in the three folk tales are related to deforestation, preservation of forest ecosystems, and due to the destruction of springs. The ecological education can be carried out in the form of oral storytelling, providing reading materials and increasing interest of reading, and the preservation of the traditions associated with the folktale. This education involves all members of society from children, youths, and adults. Learning about nature can be carried out by understanding the variety of folk tales with an environmental theme.